Project-Based Learning sebagai Strategi Inovatif Pembelajaran Bahasa Indonesia di Perguruan Tinggi: Perspektif Mahasiswa Ekonomi - Dioka Muhammad Akbar; Wahidah Halimahnur; Desi Qoriah; Umi Kulsum (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This article discusses the perceptions of students from the Faculty of Economics at Garut University regarding the implementation of the Project-Based Learning (PjBL) method in the Indonesian Language course. This quantitative study aims to measure the impact of the PjBL method on improving various aspects of students’ language skills, including critical thinking, oral and written communication, collaboration, relevance, and motivation. Data were collected through the distribution of questionnaires. The research population consisted of students from the Faculty of Economics at Garut University, with a sample of 41 students. The results indicate that students generally welcomed PjBL, considering it to make learning more relevant, interactive, and motivating. They reported significant improvements in their ability to organize ideas, analyze problems, and work collaboratively in teams. However, challenges such as time management and project complexity were also identified. These findings highlight the potential of PjBL as an innovative strategy to enrich the Indonesian Language learning experience in higher education, particularly for students from non-language backgrounds.